Talking to Shadows : Poems - Houchin, Ron (Book collections on Project MUSE., 2020)
"Wolves howl in the hollow of night, cats yowl from crags and forests, but people describe sunsets, address their dead, pray to what they feel may lie beyond the stars, and perhaps even take note of a mysterious figure recurring in an alley. In "Talking to Shadows," his ninth collection of poems, Ron Houchin replies with sensitivity and wit to things seen or sensed, offering a celebration of sights, sounds, and objects that elicit responses through the phenomena of their being. Whether evoking the presage of a coming ice age, a photo of an unknown ancestor in a family album, or the presence of nature during a lone walk across a night field, Houchin's poems converse with the shadows of existence that permeate a world filled with beauty and mystery"--